Lexicon and Grammar in the Aramaic Land Description Ostraca from Idumea - Notarius, Tania (JAOS, 2025)
This article is based on the corpus of Aramaic epigraphic cadastral documents published in Bezalel Porten and Ada Yardeni, Textbook of Aramaic Ostraca from Idumea, vol. 5 (University Park, PA: Eisenbrauns, 2023). The lexicon and syntax of these texts present a number of intriguing phenomena, and the examination of these phenomena allows the clarification of the reality behind the words. In particular, this article discusses ellipsis, omissions, and the syntax of captions as part of scribal conventions, as well as some technical terms and groups of lexemes that belong to the vocabulary of the land descriptions.